LINKING HUMAN RESOURCE COMPETENCY TO THE PERFORMANCE OUTCOMES OF MSMEs - Almas Farah Dinna Dewi; Isti Fadah; Handriyono (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
Every year, micro, small, and medium enterprises (MSMEs) play a vital role in boosting economic growth and increasing gross domestic product (GDP) in many countries, including Indonesia. Among various business categories, agroindustry-based MSMEs stand out as one of the most resilient segments within the informal sector, particularly during economic crises. This resilience was evident in various situations, including the post-COVID-19 recovery period. However, the rapid advancement of digitalization, technology, and heightened market competition has created both opportunities and challenges for small and medium-sized enterprises. To enhance their performance, it is essential to identify the key components required for developing and strengthening human resource (HR) quality in alignment with current industry demands. This study employs a descriptive research design with a quantitative approach, utilizing multiple linear regression analysis. The findings indicate that human resource competencies—namely education, skills, and abilities—significantly impact the performance of agroindustry-based MSMEs. The study focuses on a city known for its contribution to Indonesia’s agribusiness sector, with the aim of offering a replicable model for enhancing MSME performance in other agroindustry-oriented countries.